Astaxanthin and thiamine dynamics in the copepod Temora longicornis in response to ultraviolet radiation exposure - Samuel Hylander; Peter Sylvander; Rodrigo J. Gonçalves; Barbara Tartarotti; Thomas Roach; Emil Fridolfsson; Thomas Kiørboe; Pauline Snoeijs-Leijonmalm (PLoS ONE, 2025)
Several aquatic top predators suffer from deficiency in vitamin B1 (thiamine), sometimes combined with low levels of carotenoid pigments, e.g., astaxanthin. The mechanisms leading to correlations between carotenoid pigmentation and thiamine status are not known. These substances and their precursors are produced by single-celled organisms and transferred to higher trophic levels via zooplankton. However, little is known about the factors regulating this transfer process and how it is affected by environmental stressors and zooplankton diet. We therefore exposed a common copepod, Temora longicornis, to ultraviolet radiation (UVR), which is an important environmental stressor, and to food items of different quality in terms of carotenoid profile. Astaxanthin was the most abundant carotenoid found in copepods. Its concentrations were negatively affected by UVR regardless of diet type, and the availability of an astaxanthin precursor (β-carotene) in the diet did not affect the response. Thiamine, on the other hand, showed a varying response, with elevated levels in copepods exposed to UVR at low β-carotene diet and lower levels in copepods exposed to UVR and high β-carotene diet. Altogether, this indicates that astaxanthin was consumed for photoprotection in the zooplankton and that thiamine dynamics might be modulated by UVR under certain dietary conditions. Hence, the concentrations of astaxanthin and thiamine in copepods are dynamic and to some extent regulated by exposure to UVR. Thus, the ability of zooplankton to transfer these substances to higher trophic levels depends, to some extent, on the exposure to environmental stressors.